Dataset on biochemical markers and histological alterations in rat kidney intoxicated with cadmium chloride and treated with antioxidant - Esmaeil Karami; Zahra Goodarzi; Ali Ghanbari; Alireza Dehdashti; Ahmad Reza Bandegi; Sedighe Yosefi (Data in Brief, 2022)
This dataset demonstrates the in vivo renal histology and biochemical activity of Atorvastatin (AT) in cadmium-induced nephrotoxic rat model. Fifty-six adult male Wistar rats assigned to eight groups. Rats were treated with physiologic saline at a volume of 4 mg/kg, contained Atorvastatin at a dose of 20 mg/kg body weight for 15 days. The intraperitoneal administration of cadmium chloride at doses of 1, 2, 1 and 3 mg/kg started on day 8. On day 16, samples were collected for biochemical and histological analyses. Data of renal function were estimated in the serum and organ. Cadmium chloride increased malondialdehyde (MDA), blood urea nitrogen (BUN), and creatinine (Cr) serum level and decreased superoxide dismutase (SOD), glutathione peroxidase (GPx) and glutathione (GSH) levels. Administration of Atorvastatin significantly increased lipid peroxidation and renal decreased glutathione and antioxidant enzymes activity and significantly decreased BUN and Creatinine levels. Data were supported by histological examination indicated improved changes and kidney protective potential following cadmium chloride-induced oxidative stress.